The kid - Turtletaub, Jon (USA : Walt Disney [production company] ; Kuala Lumpur : Berjaya HVN Sdn. Bhd. [distributor])
Successful, high-powered Russ Duritz has spent all of his incredibly empty life forgetting the child he used to be - until one day, he meets him face-to-face
Executive producer, Arnold Rifkin ; editor, Peter Horness
Cast: Bruce Willis, Spencer Breslin, Emily Mortimer, Lily Tomlin, Chi McBride
Keywords: Comedy films; Children in motion pictures